Pembulian di dunia online: Strategi menghadapi tindakan cyberbullying - Dzakiyah, Nadiyatudz (Maliki Interdisciplinary Journal, 2024)
Cyberbullying has become a significant problem in today's digital society, especially among teenagers and children. This article discusses the forms of cyberbullying, its impact on victims, and effective strategies for dealing with it. Based on an analysis of the latest literature and case studies, this article offers practical guidance for parents, educators, and policymakers to protect children from cyber harm.